Blast protection using perimeter walls - Serdaroğlu, İhsan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
The impact of a blast scenario is studied by many researchers and the diﬀerent estimation techniques and design manuals are developed for designing against blast loads. Conducting experiments and using empirical formulae are the two methods for this estimation. The third method is the use of the computational ﬂuid dynamics tools for the calculations to obtain the peak pressures on a blast. In this study, one of those tools, Air3D, is used to determine the reﬂected pressures as well as impulses for diﬀerent geometries. Two measures to take to reduce the impact of an explosion are using blast walls and increasing the distance to the blast. The main purpose of this study to have a parametric study on both using the Air3D tool. Validation of the tool is made by comparing the results with the results of an experiment which is available in the literature and also with the readings of the design charts. Also, a sample design is made for the blast wall using design charts and procedures to make sure the wall stays in place after the blast. Then, the parametric studies are conducted with four diﬀerent wall heights and four diﬀerent wall to building distances as well as no wall cases. The results show that the increase in wall-building distance increase the protection, but in a decreasing trend. When the wall heights are considered, it is seen that blast walls protect the structures in low heights, especially along their heights, but may cause higher pressures in higher points of the structure.
Keywords: Blasting.; Buildings -- Security measures.